PERTUMBUHAN DAN TINGKAT KEMATANGAN GONAD IKAN KURO (Eleutheronema tetradactylum) DI DAERAH ESTUARI PESISIR PANTAI KOTA MERAUKE - Sunarni Sunarni; Modesta R. Maturbongs (Musamus Fisheries and Marine Journal, 2018)
Research on the growth and level maturity gonad of Kuro fish (Eleutheronema tetradactylum) in the Merauke municipal coastal estuary is very important to be done as a management effort. The purpose of research on Kuro fish bioecology in the estuary area of the coastal city of Merauke is to examine aspects of population dynamics and reproductive biology aspects of Kuro fish. The study was conducted in the Estuari area of the coastal city of Merauke for 3 months in November 2017 - January 2018. The research station was determined by purposive sampling. Based on data analysis of the relationship of weight and long known growth pattern of kuro fish is allometrik positive. The value of the Kuro fish condition factor during the study showed that it did not show any plumpness or obesity. The maturity level of kuro fish gonad from the catch obtained is all in TKG I. Fish kuro caught all male sex this is because this type of fish belongs to the hermaphrodite fish protandri. Keywords: Growth and level maturity level; Kuro Fish; Estuary.